Kinematic analysis of diving back pike somersault in platform according to players' skill level - Park, J.; Ryu, J.-S.; Park, S.; Lim, H.; Park, S.; Kim, J.; Jung, C.-H.; Yoon, S. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to investigate the kinematic difference in Back Pike somersault in platform diving according to players` skill level and to assist them to improve performances. Ten Korean diving athletes participated in this study and they were divided into skilled group (n=5) and less-skilled group (n=5) and t-test was performed to find the difference at the moment of take-off between groups. The results showed that the hip extension angle was greater and the extension velocity of knee and hip joints were faster in skilled group compared to less-skilled group. It is recommended, therefore that the flexibility training of hip joint and muscle strength training to enhance extension velocity of knee and hip joints are needed.